Analysis of learning difficulties in vertebrate zoology during the COVID-19 pandemic based on student learning styles - Wachidatul Linda Yuhanna; Riyanto; Nurmala Hindun (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
Vertebrate zoology lectures during the COVID-19 pandemic brought about a transformation from face-to-face lecture systems to online self-learning. Students with various learning styles experience difficulties in studying vertebrate zoology courses. The purpose of this study was to analyze the learning difficulties of the COVID-19 pandemic zoology vertebrate course as a whole and based on student learning styles. This research was conducted at the University of PGRI Madiun and IKIP Budi Utomo in May 2020. The number of respondents was 140 students of the Biology Education Department. This type of research is qualitative research with a survey method. The instrument used was a questionnaire analysis of vertebrate zoological learning difficulties using the google form. Data were analyzed descriptively qualitatively. The results showed that the learning difficulties of students, in general, were related to the understanding of scientific names as much as 71% and the fulfillment of teaching materials as much as 51%. The learning difficulties of students with a visual learning style consisted of understanding scientific names (69%) and the fulfillment of teaching materials (57%). The learning difficulties of students with auditory learning styles consist of understanding scientific names (81%). The learning difficulties of students with the kinesthetic learning style consisted of understanding scientific names (67%). This study concludes that students' difficulties are dominated by understanding scientific names and the availability of teaching materials.